FRI0266 Cd16+ monocyte subsets in patients with systemic lupus erythematosus, primary antiphospholipid syndrome, and antiphospholipid syndrome with lupus are associated with specific clinical/serological features of these diseases. (12th June 2018) - Perez-Sanchez, C.; Barbarroja, N.; Aguirre, M.A.; Ruiz-Limon, P.; Abalos, M.C.; Jimenez-Gomez, Y.; Arias de la Rosa, I.; Segui, P.; Ortega, R.; Collantes, E.; Escudero, A.; Le Lann, L.; et al.
Abstract : Objectives: This study, developed within the IMI-JU project PRECISESADS framework, aimed to determine the enrichment on CD14 +and CD16+monocyte subpopulations in SLE, APS and APS +SLE patients, and to investigate their role in the pathogenesis of these diseases. Methods: The frequencies of monocyte subpopulations in the peripheral blood of 54 healthy donors and 46 SLE patients included in the PRECISESADS study (preliminary data) were determined by flow cytometry. A second cohort of 21 APS +SLE patients and a third cohort of 19 APS patients were included. Clinical profile, proinflammatory circulating mediators, and peroxide levels were analysed. Carotid intima media thickness (CIMT) was evaluated as atherosclerosis marker Results: The CD14 +CD16+ (non-classical) monocyte subset was reduced in SLE patients. Their frequencies were negatively associated with the positivity for anti-dsDNA, anti-SSB, anti-SSA and anti-U1RNP autoantibodies, as well as with renal involvement, which might reflect a recruitment process of this subset in renal tissues. Correlation studies further indicated a link between the reduced frequency of non-classical monocytes and increased levels of circulating inflammatory mediators. Conversely, SLE patients with a previous history of thrombosis displayed a significant increase in circulating CD14 +CD16+monocytes in relation to those without previous thrombotic manifestations. These results prompted us to evaluate the proportion and profile of this inflammatory subtype in parallel cohorts of SLE +APS and APS patients, on which thrombosis constitute the main clinical disorder. SLE +APS patients showed enrichment in intermediate (CD14 ++CD16+) and non-classical monocytes, associated with the positivity for anti-dsDNA antibodies and the presence of atheroma plaques. Correlations among the frequency of those monocyte subsets and inflammatory mediators, and circulating cytokines, were also demonstrated. Yet, SLE +APS patients with renal involvement displayed reduced proportion of circulating intermediate and non-classical monocytes, suggesting that, as in the case of SLE patients, circulating CD16 +cells might have migrated to the kidney. In APS patients we also saw enrichment of the CD16 +inflammatory subsets, associated to recurrent thrombotic events and a pathologic CIMT, pointing out that such subsets are associated with CVD. The scores of various markers related to autoimmunity, oxidative stress and prothrombotic molecules further correlated with the proportions of intermediate and non-classical monocytes. Conclusions: Circulating CD16 +monocytes might constitute an important subpopulation of proinflammatory cells, whose frequency might identify APS, APS+SLE and SLE patients suffering thrombosis, atherosclerosis and organ involvement. Acknowledgements: Supported by: EU/EFPIA-IMI-PRECISESADS (n° 115565), Instituto de Salud Carlos III (FIS PI15/1333) and Junta Andalucia (CTS-7940). Disclosure of Interest: None declared